The Effects of seed size on germination rate and grain yield of spring wheat varieties (Mongolian Journal of Agricultural Sciences, 2022)
Seed size is an important parameter that can influence the germination, growth, and biomass of nursery seedlings and future crops. In this study, the effect of seed size on germination and grain yield was analyzed in six different wheat varieties (early maturity Darkhan-131, Darkhan-160, mid-early maturity Darkhan-34, Darkhan-193, mid-late maturity Darkhan-144, Darkhan-181). Based on diameter, the seeds were categorized into five size classes (>2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm, 2.2 mm) can be more useful for early-maturity varieties, and smaller seed sizes (>2.5 mm) are more relevant for mid-early and mid-late maturity varieties.   Буудайн тарих үрийн тохиромжтой фракцыг тогтоох ХураангуйҮрийн фракц нь хээрийн цухуйц, биомасс, ургацад нөлөөлдөг тарих үрийн чанарын чухал үзүүлэлт болно. Эндоспермдээ нөөц бодис багатай үрээс туяхан цухуйц гарах улмаар ган халуун болон тааламжгүй нөхцөлд амархан нэрвэгдэж, ургац буурах үндэс болж байна. Ургамал газар тариалангийн хүрээлэнгийн үр тарианы селекцийн секторын туршлагын талбайд зусах буудайн эрт болцтой Дархан-131, Дархан-160 дунд болцтой Дархан-34, Дархан-193, дунд оройн болцтой Дархан-144, Дархан-181 сортуудын үрийг EML200 фракцлагч машинаар